2020
DOI: 10.1007/s00167-020-05939-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with posterior capsular release, botulinum toxin injection, hamstring tenotomy, and peroneal nerve decompression improves flexion contracture after total knee arthroplasty: minimum 2-year follow-up

Abstract: Purpose No definite treatment option with reasonable outcome has been presented for old and refractory flexion contracture after total knee arthroplasty (TKA). We describe a surgical technique for 21 refractory cases of knee flexion contracture, including 12 patients with history of failed manipulation under anesthesia (MUA). Methods Retrospective review was conducted for procedures performed by a single surgeon between 2005 and 2016. Twenty‐one knees (19 patients) with knee flexion contracture after primary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…26 Although 12 of our patients (12 knees) retained mild valgus after surgery (Figure 6), none of our patients had postoperative knee instability. Hamed et al 27 reported the treatment of flexion contracture after TKA by means of hamstring release, intraoperative release of the lateral structures of the knee joint (ITB, biceps femoris), and achieved good results through a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…26 Although 12 of our patients (12 knees) retained mild valgus after surgery (Figure 6), none of our patients had postoperative knee instability. Hamed et al 27 reported the treatment of flexion contracture after TKA by means of hamstring release, intraoperative release of the lateral structures of the knee joint (ITB, biceps femoris), and achieved good results through a 2-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed flexion deformity decreased from a mean of 24° preoperatively to a mean of 2.9° after procedure. Recently, in their retrospective review, Vahedi et al (17) described a more invasive procedure. In fact, they combined posterior soft-tissue release (posterior capsule and hamstring tendons) with prophylactic peroneal nerve decompression and botulinum toxin type A injection.…”
Section: Discussionmentioning
confidence: 99%
“…88 -2 -2022 may be without clinical relevance. Nevertheless, beyond 15 degrees, it may cause severe disability and functional limitation, hence surgical treatment is required (16,17). Several procedures have been described in the literature to deal with flexion contracture after TKA persisting to the conservative treatment (15,22,23).…”
Section: Inclusionmentioning
confidence: 99%
See 2 more Smart Citations